2022
DOI: 10.3389/fonc.2022.985377
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic value of fibrinogen to albumin ratio in malignant tumor patients: A meta-analysis

Abstract: BackgroundRecent studies have shown that the fibrinogen to albumin ratio (FAR) is closely related to the prognosis of various cancers. The aim of this systematic review and meta-analysis was to investigate the prognostic value of FAR in malignancies based on the available evidence.MethodTo systematically search the Cochrane Library, Embase, PubMed, Google Scholar, Baidu scholars, CNKI and VIP databases for relevant studies published before April 1, 2022, and to evaluate the fibrinogen-to-albumin ratio (FAR) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 65 publications
1
10
0
Order By: Relevance
“…There is a pressing need for more comprehensive studies on how Fg levels may interfere with various chemotherapy regimens and impact the development of therapy resistance. Furthermore, future investigations could delve into the prognostic significance of plasma Fg ratios when combined with other tumor prognostic markers, such as the fibrinogen-to-albumin ratio ( 137 , 138 ), F-NLR (fibrinogen and neutrophil-lymphocyte ratio) ( 139 ), among others. Additionally, there is scope for further exploration of the roles played by Fg fragments, including FGA, FGB, and FGG, in the context of tumor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…There is a pressing need for more comprehensive studies on how Fg levels may interfere with various chemotherapy regimens and impact the development of therapy resistance. Furthermore, future investigations could delve into the prognostic significance of plasma Fg ratios when combined with other tumor prognostic markers, such as the fibrinogen-to-albumin ratio ( 137 , 138 ), F-NLR (fibrinogen and neutrophil-lymphocyte ratio) ( 139 ), among others. Additionally, there is scope for further exploration of the roles played by Fg fragments, including FGA, FGB, and FGG, in the context of tumor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Numbers studies have confirmed that the FAR is an important marker that reflects systemic inflammatory diseases. Some studies have shown that the FAR can be used as a prognostic indicator for coronary artery severity, stroke, cerebral haemorrhage, tumours (such as pancreatic cancer and liver cancer), COVID-19 and other diseases ( Li et al, 2022 ; Rathore et al, 2022 ; Lin et al, 2022 ). As a predictor of diabetic complications like Kidney disease and arteriosclerosis, the FAR was more effective than any single indicator ( Wang et al, 2021 , 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Liver-produced fibrinogen and albumin are useful biomarkers for inflammation and haemodynamic changes ( Chapin & Hajjar, 2015 ; Luyendyk, Schoenecker & Flick, 2019 ; Deveci & Gazi, 2021 ). Fibrinogen/albumin ratio (FAR) was more effective in predicting inflammation and tumors combined the two indicators ( Omiya et al, 2021 ; Li et al, 2022 ). Moreover, FAR is a stronger independent predictor of diabetic kidney disease than FIB and ALB ( Wang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Fibrinogen is produced by the liver as an indicator of the procoagulant state, which plays a role in inflammatory reactions at various levels [ 6 ]. Albumin is the most abundant plasma protein and an essential protein in human plasma.…”
Section: Introductionmentioning
confidence: 99%